2019
DOI: 10.1080/21655979.2019.1642722
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of long non-coding RNA H19 blocks anaplastic thyroid carcinoma growth and metastasis

Abstract: Long non-coding RNA H19 (H19) is highly expressed in cancers and is considered to highly correlate with the extent of malignant degree. The present study was performed to determine the expression levels of H19 in anaplastic thyroid carcinoma (ATC) tissues and the role of H19 in ATC 8505C cells in vitro and in vivo. Expression of H19 was detected in 19 ATC and 19 normal thyroid tissues by real-time quantitative polymerase chain reaction. Utilizing the siRNA or short hairpin RNA (shRNA) directed against human H1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“… Cell line/tumor tissue Kim/2016 LOC100507661 3q26.2 C643 8505C Up ↑ Cell proliferation, migration, and invasion a [ 11 ] Gu/2017 GAS5 1q25.1 33 Down ↑ Cell cycle progression and proliferation probably by upregulating of CDK6 ↓ Survival rate b Poor prognosis [ 12 ] Zhang/2019 H19 11p15.5 8505C SW1736 KAT18 CAL62 19 Up ↑ Proliferation, migration, and invasion ↓ Apoptosis [ 13 ] Wang/2018 UCA1 19p13.12 SW1736 KAT18 8 Up ↑ cell viability, proliferation, migration, and invasion via binding to miR-135a and regulation of c-myc expression [ 14 ] Wang/2019 HOTAIRM1 7p15.2 10 Up ↑ HOTAIRM1 expression during thyroid cancer development and progression [ 15 ] Wang/2019 PCA3 9q21.2 10 Up ↑ PCA3 expression during thyroid cancer development and progression [ 15 ] Chen/2019 HCP5 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Cell line/tumor tissue Kim/2016 LOC100507661 3q26.2 C643 8505C Up ↑ Cell proliferation, migration, and invasion a [ 11 ] Gu/2017 GAS5 1q25.1 33 Down ↑ Cell cycle progression and proliferation probably by upregulating of CDK6 ↓ Survival rate b Poor prognosis [ 12 ] Zhang/2019 H19 11p15.5 8505C SW1736 KAT18 CAL62 19 Up ↑ Proliferation, migration, and invasion ↓ Apoptosis [ 13 ] Wang/2018 UCA1 19p13.12 SW1736 KAT18 8 Up ↑ cell viability, proliferation, migration, and invasion via binding to miR-135a and regulation of c-myc expression [ 14 ] Wang/2019 HOTAIRM1 7p15.2 10 Up ↑ HOTAIRM1 expression during thyroid cancer development and progression [ 15 ] Wang/2019 PCA3 9q21.2 10 Up ↑ PCA3 expression during thyroid cancer development and progression [ 15 ] Chen/2019 HCP5 ...…”
Section: Resultsmentioning
confidence: 99%
“…In this study, targeted inhibition of H19 with siRNA decreased proliferation, migration, and invasion and increased apoptosis in ATC cell line, 8505C, in vitro and inhibited tumorigenesis and metastasis in vivo. Therefore, the H19 may be an effective target for ATC molecular therapy [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dysregulation of lncRNA H19 has been studied widely in different cancers such as bladder (114), breast (115,116) and liver (117). The dysregulation of H19 in thyroid cancer is subject of controversy since the down-regulation was reported in FTC (118) and PTC (119), while the overexpression is reported in PTC, ATC (120) and PTC/PTC stem cells (PTCSCs) (121). Given the functional studies performed in these notes, the oncogenic nature of H19 in thyroid cancer is more conceivable since H19 knockdown resulted in the suppression of proliferation, migration, and invasion in ATC cells in vitro and inhibited tumorigenesis and metastasis in vivo (120).…”
Section: Lncrnas Regulating Thyroid Carcinogenesismentioning
confidence: 99%
“…The dysregulation of H19 in thyroid cancer is subject of controversy since the down-regulation was reported in FTC (118) and PTC (119), while the overexpression is reported in PTC, ATC (120) and PTC/PTC stem cells (PTCSCs) (121). Given the functional studies performed in these notes, the oncogenic nature of H19 in thyroid cancer is more conceivable since H19 knockdown resulted in the suppression of proliferation, migration, and invasion in ATC cells in vitro and inhibited tumorigenesis and metastasis in vivo (120). Moreover, the depletion of H19 was shown to suppress the sphere formation ability (121), collectively suggest that H19 acts as an oncogene in thyroid cancer.…”
Section: Lncrnas Regulating Thyroid Carcinogenesismentioning
confidence: 99%
“…9 Increasing studies demonstrated that H19 played a positive role in the embryonic development and tumorigenesis processes in multiple cancers. For example, zhang et al discovered that H19 expression was increased and H19 knockdown largely inhibited the progression of anaplastic thyroid carcinoma cells; 10 also, H19 significantly enhanced the malignant development of HCC cells by targeting miR-22. 11 Moreover, H19 has been identified to associate with the cell progression, cell chemosensitivity, poor prognosis and cell metastasis.…”
Section: Introductionmentioning
confidence: 99%